The internet as an essential tool for the english language learning and acquisition at academic unit of administrative and humanistic sciences at Technical University of Cotopaxi during march-august 2o13 academic period. - Rueda Flores, Mayra Alexandra (2014)
Internet as an essential tool for the English language has not been used in a better way for the students from English career. The students and teachers unknown tips and web addresses to practice English. This is the principal reason that arise the necessity to create a guide which will be useful and so interesting for everybody. This investigation was justified because it will permit to develop the four skills in the students using Internet and it will be a complement for teachers making interesting and dynamic classes. Methodologically, this investigation was developed at Technical University of Cotopaxi during the academic cycle March-August 2012 with the participation of students and teachers from English career applying the technique of the survey. In conclusion with the use of technology the students will develop the four skills in an interactive lab and it also will help teachers to make an interesting class using Internet as an essential tool for the English Language Learning and Acquisition.